Effect of pirenzepine, a muscarinic M-1 receptor antagonist, on amygdala kindling in rat - (:unkn) unknown (ELSEVIER SCIENCE BV, 1999)
Kindling, an animal model of complex partial seizures with secondary generalization, is performed by daily application of low-intensity electrical brain stimulation. The purpose of this study was to investigate the role of muscarinic M-1 receptors on amygdala kindling in the rat. Bipolar nichrome stimulation and recording electrodes were stereotaxically implanted into the right and left basolateral amygdala. Extradural recording electrodes were also placed bilaterally in the skull over the cortex. Amygdala stimulation was applied twice daily at the current intensity of afterdischarge threshold. Seizure intensity was graded by using Racine's standard five-stage scale. In the first group of experiments, saline or pirenzepine (10, 25, 50 and 100 nmol), a muscarinic M-1 receptor antagonist, was injected intracerebroventricularly 1 h before the electrical stimulation. In the second group of experiments, rats were kindled to full stage 5 seizures. After a recovery period, 50 nmol of pirenzepine was administered intracerebroventricularly to kindled animals. In the first group of experiments, none of the animals pretreated with the doses of 50 and 100 nmol of pirenzepine reached a stage 5 seizure. Pirenzepine significantly retarded kindling seizure development and increased the total number of stimulations required to reach the first stage 5 seizure. Afterdischarge duration was also reduced in the pirenzepine 10 nmol group as compared with that in the saline-pretreated group. In the second group, seizure stage and afterdischarge duration were not affected by pirenzepine in fully-kindled animals. The findings of this study suggest that muscarinic M-1 receptors may have a critical role in the development of kindling epileptic activity, but not in already kindled seizures. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: kindling; epileptogenesis; amygdala; rat; acetylcholine; muscarinic receptors; UNION-OF-PHARMACOLOGY; EPILEPSY; SEIZURE; MODEL; CLASSIFICATION; SUPPRESSION; HIPPOCAMPUS; MECHANISMS; GENES; M1